Efektivitas Pelatihan Perencanaan Karir terhadap Peningkatan Efikasi Diri dalam Pengambilan Keputusan Karir - Nurlaely Izzawati; Lisnawati Lisnawati (University of Merdeka Malang, 2015)
This reserach aimed to determine the effectiveness of the training of career planning to improves the self efficacy in career decision making. As the design of study, the research used randomized pre test post test with control group design. This study used 30 students as the subjects, which divided into two groups: 15 subjects as the experimental group and 15 subjects as the control group. Scale of the self efficacy incareer decision making was used to collecting the data, which was prepared by researcher. The results of the analysis using the Independent Sample t-Test showed that, t= 4.412 and p=0,000 (p0,05). The results of the analysis using thePaired Sample t-Test showed that, t=-6.400 and p=0,001 (p0,05). Therefore, it can be concluded that the training of the career planning could be increased the self efficacy in career decision making.